A multipurpose panel of microhaplotypes for use with STR markers in casework. (September 2022) - Kidd, Kenneth K.; Pakstis, Andrew J.; Gandotra, Neeru; Scharfe, Curt; Podini, Daniele
Abstract: A small panel of highly informative loci that can be genotyped on the same equipment as the standard CODIS short tandem repeat (STR) markers has strong potential for application in forensic casework. Single nucleotide polymorphisms (SNPs) can be typed by a couple of methods on capillary electrophoresis (CE) machines and on sequencers, but the amount of information relative to the laboratory effort has hindered use of SNPs in actual casework. Insertion-deletion markers (InDels) suffer from similar problems. Microhaplotypes (MHs) are much more informative per locus but have similar technical difficulties unless they are typed by massively parallel sequencing (MPS). As forensic labs are acquiring sequencing machines, MHs become more likely to be used in casework, especially if multiplexed with STRs. Here we present the details of a multipurpose panel of 24 MHs with the highest effective number of alleles (Ae ) from previous work. An augmented STR panel of 24 loci (20 CODIS markers plus four commonly typed STRs) is also considered. The Ae and ancestry informativeness (In ) distributions of these two datasets are compared. The MH panel is shown to have better individualization and population distinction than the augmented CODIS STRs. We note that the 24 MHs should be better for mixture analyses than the STRs. Finally, we suggest that a commercial kit including both the standard CODIS markers and this set of 24 MH would greatly improve the discrimination power over that of current commercial assays. Highlights: A small panel of 24 highly informative microhaplotype loci has been identified. The MH panel is good for individualization, ancestry inference, and mixture analysis. The MHs are more informative than the 24 augmented CODIS STRs typed by CE. The 24 MH panel is good enough to be a stand-alone panel for forensic casework.